CFD analysis of added mass, damping and induced flow of isolated and cylinder-mounted heave plates at various submergence depths using an overset mesh method. (February 2022) - Pinguet, Romain; Benoit, Michel; Molin, Bernard; Rezende, Flavia
Abstract: Fluid–structure interaction processes of heave damping plates in forced vertical motion are investigated using a CFD numerical model. First, a single isolated disk is considered with two submergence depths, including a case where the disk is very close to the mean water level with d / D = 1 / 12 ( d is the submergence depth and D the diameter of the disk). Then, the case of a disk attached to a vertical cylinder is analyzed, corresponding to one leg of a semi-submersible floater. The open source software OpenFOAM® is used to model the flow around the disk and to extract the relevant hydrodynamic coefficients of the structures. The dynamics of the structure and induced flow and free surface waves are tackled with the overset mesh tool implemented in OpenFOAM®. Considering the rotational symmetry of the problem, an axisymmetry model is used with wedge symmetry boundary conditions. The results are compared with experimental measurements and linearized potential flow modeling approaches with empirical correction. The CFD results of the models of both structures predict well the experimental measurements, including large oscillation periods and various amplitudes of heaving motion, where the potential model results are deteriorated. Highlights: CFD with overset mesh method can predict the flow around heaving thin plates. Good agreement with measured forces for a large range of amplitudes and periods. Vorticity and damping viscous effects are well captured by CFD. CFD predicts added mass better than linear model for plates close to the free surface. Negative added mass coefficients are computed at certain oscillation periods.